Enhanced photocurrent properties of Dye/Au-loaded TiO2films by grating-coupled surface plasmon excitation - Hathaithip Ninsonti (2018)
We report enhanced photocurrent properties of dye/Auloaded titanium dioxide (TiO2) films on Au gratings. Au-loaded TiO2nanopowders were first synthesized by a modified sol-gel method and then prepared by the impregnation method. We also fabricated dye-sensitized solar cells, which were composed of Au grating/Au-TiO2/TMPyP-SCC LbL (20 bilayers)/ electrolyte/ITO substrates. Short-circuit photo-current measurements showed that Au-loaded TiO2with grating-coupled surface plasmon excitation can enhance the short-circuit photocurrentof the fabricated cells. Copyright © 2013 The Institute of Electronics, Information and Communication Engineers.